FUZZY ANALYSIS DAN MATRIKS RESIKO KEBAKARAN DI GEDUNG KAMPUS FAKULTAS TEKNIK UNIVERSITAS PASUNDAN - Riza Fathoni Ishak; Toto Supriyono; Deden Syarifudin (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2024)
The security and safety of lecturers, employees and students is one important aspect that needs to be guaranteed by campus managers, so that the implementation of the academic process can run comfortably and safely. The condition of the building is quite old, the condition of the Light Fire Extinguisher (APAR) is also not feasible, the condition of the emergency stairs is still used in general, there is no special evacuation emergency stairs, fire detection equipment is not functioning. Dimensions of Emergency Equipement, and Hazard Detectors, Emergency Planning, Building Facilities Safety Fire, and Equipment Potential Fire, as variables that will be measured using Fuzzy Analysis to produce weighting values and priorities for fire management management, with the weight value of Emergency Equipement, and Hazard Detectors is 0.48 as priority 1 in the future that needs to be improved.... Based on the fire risk assessment of the Faculty of Engineering building on Jl.Setiabudi involving the building area (lectures, lecturer rooms, and laboratories) and outside the building open areas and parking lots. Through a limited purposive sampling approach, the fire risk value for open areas is in the value of 6 medium risk categories, for teaching and lecturer rooms in the range of 4-9 high risk categories, while the laboratory area is in the range of 4-8 high risk categories. The maintenance aspect of fire detection and handling equipment is a suggestion for future building managers of the Faculty of Engineering Unpas.